Hearing loss in mice with disruption of auditory epithelial patterning in the cochlea - Katsunuma, Sayaka; Togashi, Hideru; Kuno, Shuhei; Fujita, Takeshi; Nibu, Ken-Ichi (Frontiers in Cell and Developmental Biology, 2022)
In the cochlear auditory epithelia, sensory hair and supporting cells are arranged in a checkerboard-like mosaic pattern, which is conserved across a wide range of species. The cell adhesion molecules nectin-1 and nectin-3 are required for this pattern formation. The checkerboard-like pattern is thought to be necessary for auditory function, but has never been examined. Here, we showed the significance of checkerboard-like cellular pattern in the survival and function of sensory hair cells in the cochlear auditory epithelia of nectin-3 knockout (KO) mice. Nectin-3 KO mice showed progressive hearing loss associated with degeneration of aberrantly attached hair cells via apoptosis. Apoptotic hair cell death was due to the disorganization of tight junctions between the attached hair cells. Our study revealed that the checkerboard-like cellular pattern in the auditory epithelium provides a structural basis for ensuring the survival of cochlear hair cells and hearing function.